Comparative pyrolysis characteristics of representative commercial thermosetting plastic waste in inert and oxygenous atmosphere. (15th June 2019) - Chen, Ruiyu; Li, Quanwei; Xu, Xiaokang; Zhang, Dongdong
Highlights: Thermal degradation in inert and oxygenous atmosphere is studied by TGA. Activation energy is obtained using four popular model-free methods. Reaction mechanism and volatile products are analyzed by FTIR. Conversion rate decreases in oxygenous atmosphere instead of inert atmosphere. Two pyrolysis stages are divided in both of inert and oxygenous atmosphere. Abstract: Combustion (pyrolysis with oxygen) and pyrolysis without oxygen are two potential methods to deal with thermosetting plastic waste. To evaluate which is preponderant to recycle thermosetting plastic waste and provide guidance for optimization of product yield by pyrolysis, the pyrolysis characteristics of one representative commercial thermosetting plastic waste (phenolic glass fibre reinforced plastic, phenolic GFRP) in inert and oxygenous atmosphere are comparatively investigated employing thermogravimetric analysis (TGA), in situ Fourier transform infrared (FTIR) and online TGA-FTIR in the present study. The activation energy at different conversion rate is calculated using Tang, Senum-Yang, advanced Vyazovkin and DAEM method. Results indicate that conversion rate decreases with temperature from approximately 460 K to 550 K in oxygenous atmosphere instead of inert atmosphere. The conversion rate in inert atmosphere is larger than that in oxygenous atmosphere from 0 to 0.25, but is less than that in oxygenous atmosphere from 0.25 to 1. The maximum reaction rate in inert atmosphere varies little with heating rate, but decreases with heating rate in oxygenous atmosphere. The pyrolysis process may be divided into two stages with threshold of approximately 600 K and 550 K in inert and oxygenous atmosphere, respectively. The average value of activation energy is 172.92 kJ/mol and 115.04 kJ/mol in inert and oxygenous atmosphere, respectively. Water vapour, alcohols, aromatic compounds, aliphatic compounds, carbon dioxide, carbon monoxide, carboxylic acids and ammonia occur in the volatile products. Alcohols and aliphatic compounds mainly occur in the first stage, while aromatic compounds, carbon dioxide, carbon monoxide and carboxylic acids mainly occur in the second stage. As to water vapour and ammonia, they mainly occur in the first and second stage in inert and oxygenous atmosphere, respectively. More carbon dioxide, carbon monoxide and ammonia are generated in oxygenous atmosphere than those in inert atmosphere. Besides, more amorphous carbon is generated in inert atmosphere than that in oxygenous atmosphere.